Cost-benefit analysis of agroecological interventions in green leafy vegetable business models in Kiambu County, Kenya - Onyango, Kevin; Ndiwa, Aurillia Manjella; Bolo, Peter; Wanyama, Rosina; Chege, Christine (2024)
There is a global consensus that agroecology is a sustainable approach for agriculture and food system transformation. This is largely through harnessing nature’s resources while minimizing adverse environmental effects and improving connectivity, knowledge co-creation and inclusive relationships among food system actors. However, there is limited evidence on whether this approach is economically viable, especially for the majority of low-income value chain actors like smallholder farmers. This study therefore sought to assess the costs and benefits of integrating selected agroecological innovations in green leafy vegetable (GLV) value chains in Kiambu County, Kenya. The study focused on three GLV business models with potential for agroecological transition – one input based and two output based models. The agroecological interventions assessed include a physical expansion of agribusiness enterprises to increase production capacity and diversity, introduction of out-grower model for increased organic input production, adoption of a participatory guarantee system (PGS) for food quality assurance, adoption of collective organic production and marketing for food safety, and improved linkages among value chain actors through communication, coordination and knowledge sharing. The study applied a cost-benefit analysis (CBA) in the assessment. Net Present Value (NPV), Internal Rate of Return (IRR), and the Benefit-Cost Ratio (BCR) were applied as the evaluation criteria for the economic CBA. Additionally, thematic analysis was used to assess the social and environmental costs and benefits of the interventions in the three business models. At farm level, the results show a positive NPV across all the three models ranging from USD 130 to USD 1554, an IRR of 85% to 220%, and a BCR of 2.0 to 3.1. Similarly, at business level, the results show a positive NPV ranging from USD 320 to USD 9,684, an IRR of 24% to 29% and a BCR of 1.0-1.9. However, farm-level interventions have a shorter payback period compared to business level interventions. This shows that agroecology is economically viable at both farm and business levels. Results from the qualitative assessment also show perceived positive social and environmental outcomes of the selected interventions, implying that integration of agroecological interventions in food value chains has the potential to contribute positively to the overall food system transformation.